a) $(a + 1)^2 - 2(a + 1) + 1$
Заметим, что это выражение имеет вид $(x-1)^2$ где $x = (a+1)$.
$(a + 1)^2 - 2(a + 1) + 1 = ((a + 1) - 1)^2 = a^2$
б) $(m - n)^2 + 2n(m - n) + n^2$
$(m - n)^2 + 2n(m - n) + n^2 = m^2 - 2mn + n^2 + 2mn - 2n^2 + n^2 = m^2$
в) $(p - q)^2 - 2(p^2 - q^2) + (p + q)^2$
$(p^2 - 2pq + q^2) - 2p^2 + 2q^2 + (p^2 + 2pq + q^2) = p^2 - 2pq + q^2 - 2p^2 + 2q^2 + p^2 + 2pq + q^2 = 4q^2$
г) $(x + 2y)^2 + 2(x^2 - 4y^2) + (2y - x)^2$
$x^2 + 4xy + 4y^2 + 2x^2 - 8y^2 + 4y^2 - 4xy + x^2 = 4x^2$
Ответы:
a) $a^2$
б) $m^2$
в) $4q^2$
г) $4x^2$